Mechanism of action of Xipayimaizibizi oral liquid on outlet obstruction-induced overactive bladder: An integrated study - Menglu Wang; Yang Yang; Yuhang Du; Jiamei Xie; Yige Zhao; Yongcheng An; Ziyi Shan; Shenyujun Wang; Meng Hao; Baosheng Zhao (Journal of Traditional Chinese Medical Sciences)
Objective: To observe the effect of Xipayimaizibizi oral liquid (XP) in an overactive bladder (OAB) experimental rat model and to explore its pharmacological mechanisms. Methods: Network pharmacology was used to explore the potential mechanisms of action of XP. The rats underwent bladder outlet obstruction surgery and were administered the corresponding drug concentrations by gavage for 4 weeks. The study observed the body weight, water intake, bladder and kidney indices (to evaluate their general status), urination behavior pattern (to observe frequency and urgency), and urodynamics (to measure bladder parameters). Hematoxylin and eosin and Masson's trichome staining were used to observe changes in the bladder structure. Enzyme-linked immunosorbent assay was used to measure the levels of nerve growth factor, brain-derived neurotrophic factor, and acetylcholine in the urine. The key targets involved in these mechanisms were validated using reverse transcription-quantitative polymerase chain reaction, immunohistochemistry, and western blot in vivo/vitro experiments. Result: Network pharmacological analysis predicted that XP may alleviate OAB by affecting the cholinergic synapse and calcium signaling pathways. XP treatment significantly reduced the bladder index, improved urine behavior and urodynamic parameters, decreased the neurotransmitters in urine, and reduced the thickness of the bladder wall and collagen ratio. These results indicate that XP can alleviate OAB symptoms and improve the bladder structure. In vivo/vitro experiments further demonstrated that XP can inhibit targets, such as muscarinic acetylcholine receptor 2, and participate in cholinergic synapses to further regulate the parasympathetic nervous system. It can also reduce the overexpression of Ca2+ caused by agonists, inhibit targets such as transient receptor potential vanilloid type 1, and participate in calcium signaling pathways to maintain Ca2+ homeostasis. Conclusion: These results suggest that XP inhibited bladder overactivity by maintaining Ca2+ homeostasis and regulating the parasympathetic nervous system.